STRATEGY FOR THE IMPLEMENTATION OF NURSING DOCUMENTATION IN THE HOSPITAL ROOM GENERAL HOSPITAL MITRA SEJATI MEDAN JOHOR SUB-DISTRICT MEDAN CITY IN 2020 - yuni vivi santri (Jurnal Kajian Kesehatan Masyarakat, 2020)
Documentation of nursing care is a record of the client's response to the implementation of nursing activities as a whole, systematic and structured as accountability for actions taken by nurses against clients in carrying out nursing care. One effort to find out the right strategy for the company is a SWOT analysis. In the SWOT analysis, there is an analysis of the internal environment, namely strengths and weaknesses, and an analysis of the external environment, namely opportunities and threats. The purpose of this research was to analyze the strategy in implementing nursing care documentation in the inpatient room of Mitra Sejati Hospital, Medan Johor District, Medan City based on the SWOT analysis. This type of research used qualitative methods using a case study approach. The informants in this research were determined to be two, namely key informants and main informants. Data analysis techniques that used in this study were SWOT analysis, IFAS Matrix, EFAS Matrix and SWOT Matrix. Data collection methods in this research are books, articles, papers, regulations, focus group discussions and in-depth interviews. The results of the research are based on the SWOT analysis, IFAS Matrix, EFAS Matrix and SWOT Matrix that hospitals are in the first quadrant which is in the aggressive direction and the strategi used is strength-opportunity (SO) strategy as an effort to improve the completeness of nursing care documentation, namely; 1. Providing training and seminar support outside the hospital related to the implementation of nursing care documentation to increase knowledge and fulfillment of standards, 2. Arranging plans for updating the standard operating procedures (SOP) for implementing documentation in accordance with the available accreditation regulations and 3. Developing infrastructure for implementing documentation of care nursing according to technological progress.